Potret IPO di Bursa Efek Indonesia - Zaenal Arifin (Jurnal Siasat Bisnis, 2010)
This study analysed the IPO (Initial Public Offering) of Indonesia Stock Exchange (ISE) during 1990-2008. In line with developed countries, the study found phenomena of under pricing as well as hot and cold IPO. The magnitude of under pricing phenomena was not related to the number of companies which did the IPO. The hot IPO condition emerged after the economic crisis that was in the period of 1999-2002 and in 2006-2007, whereas cold IPO condition took place before the economic crisis that was year of 1990, 1992 and 1994-1996. In the cold period, average value of under pricing was 5.7%, while in the condition of hot IPO, the average value became 44.6%Keywords: IPO, under pricing, hot IPO, cold IPO, Indonesian capital market